Beragam Teori Kecerdasan, Proses Berpikir dan Implikasinya terhadap Pembelajaran Pendidikan Agama Islam - Kurnia Muhajarah (Jurnal Pendidikan, Sains Sosial, dan Agama, 2022)
The existence of a theory of intelligence gives a greater opportunity to develop students' abilities. If this intellectual theory can work optimally to identify and develop the multiple abilities in each student, it will create diverse forms of Islamic religious learning. Therefore, the learning of Islamic religious education concerns how (how) to make it possible for students to learn easily and is motivated by their will to learn what (what is necessary) are realized in the program as the needs of the learners are and are taught using based learning methods. intelligence to achieve maximum learning results. This study aims to (1) reveal what intelligence is, what factors affect intelligence, the theory of intelligence from thought processes; and (2) what is the meaning of the concept of intelligence, what factors affect intelligence, and the theory of intelligence from the thought process in learning Islamic religious education. This study is a qualitative study with data collection techniques using library research (library research) based on a descriptive approach. The results of this study are as follows: First, intelligence is no longer understood solely in intellectual terms. There are several types of intelligence. Second, the concept of intelligence remains relevant as a reference and basis for learning Islamic religious education. In the learning process of Islamic religious education, the development of intelligence focuses not only on reason (cognitive aspect), but also on morality (emotional aspect) and charity (psychological aspect). Of course, this has positive implications for the learning process of Islamic religious education.